Firm bankruptcies and start-up activity in Switzerland during the Corona crisis - Florian Eckert; Heiner Mikosch (ETH Zurich, KOF Swiss Economic Institute, 2021)
This paper examines the incidence of firm bankruptcies and start-ups in Switzerland based on unique register data. We propose to assess the frequency of bankruptcies over time using the concept of excess mortality. During the Corona crisis in 2020 and the first half of 2021, bankruptcy rates were substantially lower and the number of new firm formations was substantially higher as compared to the precrisis period. This holds across most industries and regions. The Great Recession and the Swiss Franc Shock showed reverse patterns. Bankruptcies dropped more in industries and cantons, in which the share of firms who received a Covid-19 loan is comparatively high. The strong start-up activity is driven by industries where the pandemic induced structural adjustments.
hdl:20.500.11850/516953
Keywords: E32; G33; M13; 330; Firm Bankruptcies; Insolvencies; Excess Mortality; Firm Formations; Start-Ups; Switzerland; Corona Crisis; Industry-Level; Canton-Level